Australian Mobility Report Cards: Which Universities Admit the Most Disadvantaged Students?. (15th July 2021) - Leigh, Andrew
Abstract: Tertiary education has a vital role to play in fostering social mobility. To assess the extent to which Australian universities enrol disadvantaged students, I use two measures of disadvantage: neighbourhood characteristics and individual characteristics, and compare higher education institutions. Neighbourhood metrics appear to be a poor proxy for individual disadvantage. Yet even so, some institutions stand out as more effective pathways for disadvantaged students. I conclude with some recommendations for improving data quality, education policy and evaluation in order to make Australian universities more effective engines of social mobility .